High‐mobility flexible thin‐film transistors with a low‐temperature zirconium‐doped indium oxide channel layer. Issue 6 (29th April 2016) - Xiao, Peng; Dong, Ting; Lan, Linfeng; Lin, Zhenguo; Song, Wei; Song, Erlong; Sun, Sheng; Li, Yuzhi; Gao, Peixiong; Luo, Dongxiang; Xu, Miao; Peng, Junbiao
Abstract : Thin film transistors (TFTs) with zirconium‐doped indium oxide (ZrInO) channel layer were successfully fabricated on a flexible PEN substrate with process temperature of only 150 °C. The flexible ZrInO TFT exhibited excellent electrical performance with a saturation mobility of as high as 22.6 cm 2 V –1 s –1, a sub‐threshold swing of 0.39 V/decade and an on/off current ratio of 2.5 × 10 7 . The threshold voltage shifts were 1.89 V and −1.56 V for the unpassivated flexible ZrInO TFT under positive and negative gate bias stress, respectively. In addition, the flexible ZrInO TFT was able to maintain the relatively stable performance at bending curvatures larger than 20 mm, but the off current increased apparently after bent at 10 mm. Detailed studies showed that Zr had an effect of suppress the free carrier generation without seriously distorting the In2 O3 lattice. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : The higher bending properties and higher mobility is still the main objective for the next flexible oxide thin‐film transistors (TFTs). In this work, high performance low‐temperature flexible ZrInO TFTs were successfully fabricated on a polyethylene naphthalate (PEN) substrate.